COVID-19 vaccine implementation at a syringe services program: experiences of frontline staff - Marina Plesons; Sabrina E. Soto Sugar; Rutendo Chimbaru; Giuliano McDonald; Lily Friedman; Ernest Thompson; Angela R. Bazzi; Hansel E. Tookes; Tyler S. Bartholomew (BMC, 2024)
Abstract Background While people with substance use disorders, including people who inject drugs (PWID), experience increased risk for COVID-19 infection and adverse outcomes, COVID-19 vaccination rates among PWID are consistently lower than those observed in the general population. Offering COVID-19 vaccines at syringe services programs (SSPs) has been proposed as a critical strategy to increase vaccine uptake among this population. We explored the experiences of frontline staff at an SSP in Miami, Florida implementing onsite COVID-19 vaccines. Methods Between June and July 2022, we conducted in-depth semi-structured interviews with 17 staff members of an SSP in Miami, Florida. Data collection and codebook thematic analysis of transcribed interviews were guided by the Consolidated Framework for Implementation Research (CFIR). Results Facilitators and barriers of COVID-19 vaccine implementation at the SSP aligned with all major CFIR domains. Key facilitators included the SSP's established partnership with the local health department for vaccine distribution, its existing funding sources which could be leveraged for vaccine-related expenses, consensus among staff about the need for new strategies to increase vaccine uptake among PWID, and PWID's trust in the SSP. Major-but largely modifiable-barriers included lack of participant compensation, limited internal collaboration and communication regarding the vaccine initiative beyond implementation leads and innovation deliverers due to competing priorities and segmented roles and responsibilities, and insufficient involvement of the most participant-facing staff (i.e., the SSP's peer navigators and outreach workers). Conclusions Implementing onsite COVID-19 vaccines was perceived as feasible and acceptable by frontline staff at the SSP, however contextual factors impeded optimal implementation. Multilevel strategies, such as participant compensation for vaccine completion and internal educational meetings with staff to improve vaccine implementation and reach, are required. As a trusted source of preventative services for PWID, SSPs are an underutilized venue for increasing vaccine uptake among this population, and findings from this study could inform the expansion of low-barrier vaccine services at SSPs nationwide.